The Export-Import Bank - Patterson, Gardner (Quarterly Journal of Economics, 1943)
Genesis and organization of the Bank, 65. — The experimental period: the first two years, 68; development of lending policies, 68; extension and further developments, 71. — The period of Scandinavian credits: the "Finnish Loan Bill, " 74; the Norwegian, Swedish, and Danish loans, 75. — The period of Latin American credits: the Act of 1940, 76; transportation loans, 78; the Brazilian Steel loan, 79; the Brazilian Economic Agreements, 80; Haiti and Ecuador, 80; Bolivia, 81; credits to Central Banks, 81. — Conclusions: aid to exporters, 85; economic development, 87; opportunities ahead, 88.